The impact of the industry 4.0 (as a whole) in supply chains - Palma, Gonçalo José Canhoto da (2019)
In the business world of today, costumers increasing demands are pushing the companies to take advantage of technology to optimise their operations, products and services. We are now watching live as the Fourth Industrial Revolution takes place built on the ongoing digital revolution. This paper studies the Industry 4.0 and its possible practical applications in the Supply Chain Management. The concepts of Industry 4.0 and Supply Chain 4.0 and its different components will be scrutinised, and potential benefits and future of this trends exhibited. Additionally, an investigation will be conducted to better understand the level of awareness of the current industrial workforce for these ongoing trends.